Emotional and behavioural difficulties in children referred for learning disabilities from two Arab countries: A cross-cultural examination of the Strengths and Difficulties Questionnaire. (January 2015) - El-Keshky, Mogeda; Emam, Mahmoud
Highlights: In summary, the cross cultural examination of the SDQ in two Arab samples showed that the three factor model showed a better model fit and provided the best representation of the instrument's latent structure. The model included an externalization and internalization dimension and a meaningful positive social dimension. The study findings indicated that the Arabic version of the SDQ has good psychometric properties and functioned well and equivalently across two Arabic cultures as well as gender. A replication of the study in similar Arab contexts is recommended in order to increase the confidence in the use and interpretation of the SDQ scores in the culturally diverse clinical samples of the Arab context. Abstract: The Strengths and Difficulties Questionnaire (SDQ) is a widely used child mental health questionnaire with five hypothesized subscales. There is theoretical and preliminary empirical support for combining the SDQ's hypothesized emotional and peer subscales into an 'internalizing' subscale and the hypothesized behavioural and hyperactivity subscales into an 'externalizing' subscale (alongside the fifth prosocial subscale). We examined both structures using the teacher informant version data from two Arab countries, namely Saudi Arabia (323) and Oman (439). Multigroup CFAs based on structural equation modelling revealed culture invariance for the SDQ. The three-factor model showed a better description of the SDQ structure. The analysis also revealed gender invariance for the SDQ three and five factor models in both the Omani and Saudi samples. There were gender differences in all the three and five factors between the Saudi and Omani samples.